Challenges of the changing Arctic continental shelf, navigation, and fisheries - Nordquist, Myron H.; Moore, John Norton, 1937-; Long, Ronán J. (Center for Oceans Law and Policy ;, 2016)
The law and policy for the Arctic are increasingly of international interest, largely due to the melting of the Arctic ice capitolo Challenges of the Changing Arctic: Continental Shelf, Navigation, and Fisheries includes contributions from global specialists dealing with the geomorphologic context, maritime delimitation and specialized topics raised by promising oil and gas prospects, particularly in the extensive continental shelf presented by Russia to the Commission on the Limits of the Continental Shelf. Arctic shipping has entered a novel, untested phase with keen interest in the opening of ice free shipping lanes and proposed regulatory regimes. Fish in the North Atlantic are moving north disrupting historic fishing patterns as well as traditional fish stocks. Agreements on the allocation of shared fish stocks pose significant management challenges. Both littoral and non-littoral user nations are concerned with maritime security as well as search and rescue preparations given the anticipated increased use of the Arctic Ocean. These and many other of the most pressing issues are addressed in this important volume, making it a must-read for all those interested in environmental law and the law of the sea.